Optimalisasi Manajemen Bandwidth Pada Jaringan Internet Politeknik Negeri Pontianak - Yasir Arafat; Tri Bowo Atmojo; Pausta Yugianus (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2023)
Pontianak State Polytechnic (Polnep) as one of the vocational education institutions that uses the internet network as a means of supporting the teaching and learning process and institutional administrative activities. Polnep gives internet access rights to all students as long as they are active students. In addition, Polnep also provides internet access rights to all employees and employees in an effort to support the teaching and learning process. Bandwidth usage on the internet network at the Pontianak State Polytechnic currently has an uneven internet access speed. Related to this problem, an authentication system for wireless network users is designed using RADIUS (Remote Authentication Dial-In User Service) technology which aims to centrally authenticate, authorize, and register user accounts in accessing the network. The RADIUS server supports multi-user and multi-roaming, making it easier for users to move to each access point without re-registering. With this Radius system, it is expected to maximize bandwidth usage evenly on all network devices at the Pontianak State Polytechnic.